Macroeconomic perspective on constructing financial vulnerability indicator in China - Kuek, Tai-Hock; Puah, Chin-Hong; Arip, M. Affendy; Habibullah, Muzafar Shah (Journal of Business Economics and Management, 2021)
This paper attempts to develop a financial vulnerability indicator for China as a barometer for the state of financial vulnerability in the Chinese financial market, possibly for real-time application. Twelve variables from different sectors are utilised to extract a common vulnerability component using a dynamic approximate factor model. Through the implementation of a Markovswitching Bayesian vector autoregression (MSBVAR) model, the empirical results indicate that a high-vulnerability episode is associated with substantially lower economic activity, but a low-vulnerability episode does not incur substantial changes in economic activity. Notably, the constructed indicator can serve as a real-time early warning system to signify vulnerabilities in the Chinese financial market.First published online 20 November 2020